Fekete-Szegö Problem for a Subclass of Meromorphic Functions Defined by the Dziok-Srivastava Operator (Communications in Mathematical Research, 2019)
By using the hypergeometric function defined by the Dziok-Srivastava operator, a new subclass of meromorphic function is introdued. We obtain Fekete-Szegöinequalities for the meromorphic function $f(z)$ for which $α-\dfrac{1+α\bigg\{1+\dfrac{z[_lI_mf(z)]''}{[_lI_mf(z)]'}\bigg\}}{\dfrac{z[_lI_mf(z)]'}{_lI_mf(z)}}$ $\precφ (z)$ $\Big(α\in{\bf C}-\Big\{\dfrac{1}{2},\,1\Big\}\Big)$.